GROWTH AND BIOCHEMICAL COMPOSITION OP POSTEMBRYONIC CARP TREATED WITH YEAST - Das, B C (Indian Journal of Fisheries, 2011)
BREWERS' yeast, an ascomycetous fungus (Sacchawniyces cerevisiae),promotes the growth of postembryonic Indian carp [species La^eo rohita(Ham.), family Cyprinidae] (Das, 1960 Z>; 1964; 1965 b). The dry weight ofcarp treated daily during the first two weeks of postembryonic Ufe is doubleor triple that of untreated control carp. The effect of yeast is dependent ondosage, within the range of 0-05 to 0-22 g per litre of water containing 50 to70 young carp. Higher dosages, within the range of 0;22 to 0-44 g, do notyield weight increase beyond those obtained at 0-22 g (Das, 1965 b). Havingestablished the beneficial effect of yeast on growth of postembryonic carp^the next problem is to determine how or in what way yeast accomplishes itseffect. For this purpose, an experimental study of the total protein, nonproteinnitrogen, acid phosphatase and alkaline phosphatase of postembryoniccarp has been carried out.MATERIALS AND METHODSOne-day-old Labeo rohita were